Secondary Metabolites in Maca as Affected by Hypocotyl Color, Cultivation History, and Site - Clément, C.; Diaz, D.; Manrique, I.; Avula, B.; Khan, I.A.; Ponce Aguirre, D.D.; Kunz, C.; Mayer, A.C.; Kreuzer, M. (Wiley, 2010)
Maca (Lepidium meyenii Walpers) hypocotyls are reported to have a favorable biological activity in man. The presumed bioactive constituents seem to vary among maca hypocotyl color types, but the residual variation is large. This study tested the hypothesis that, apart from color types, environmental factors have a distinct influence on the concentration of characteristic secondary metabolites in maca. In a field experiment at 4100 m altitude (Peru), maca of four hypocotyl color types was evaluated at two sites with different soil types. At each site, experimental areas were either never cultivated or cultivated with maca 2 to 3 yr ago followed by a fallow period. Applying four color replicates per site and area resulted in 64 plots (100 plants plot(-1)). Especially, color type largely influenced concentrations of macaene, macamides, beta-sitosterol, campesterol, and glucosinolates. Site (also clearly affecting growth yield) was weaker in effect on these metabolites but still significantly influenced concentrations of some constituents, while the effect of cultivation history was widely absent. Macaene, macamides, and beta-sitosterol were negatively correlated with glucosinolates. This shows that environmental conditions and color type have to be considered in producing maca with high concentrations of distinct bioactive metabolites.